Sistem Pakar Perancangan Instalasi Listrik Dengan Delphi 7 - Bagus Dwi Cahyono; Gigih Priyogi (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2023)
This research is motivated by the lack of optimal learning in the Electrical Power Installation subject by using a whiteboard as a learning medium. This research is a type of development research which aims to produce a product design in the form of a Borland Delphi 7 based expert system which will be used in the Electrical Power Installation subject. This learning media contains material on electrical power installations and an expert system for determining power needs, security and light points. This research was conducted in July 2021 at Sultan Ageng Tirtayasa University. The design for developing this learning media follows the ADDIE stages (Analyze, Design, Development, Implementation, Evaluation). Validation of this expert system includes content validation and design validation. Based on the results of data analysis, it is known that the expert system developed in this research has very high validity values in the two aspects assessed. For material validity it is 3.61 and media validation is 3.6 so it can be concluded that this expert system can be declared suitable for use to support learning.